Clinical evaluation of plasma exchange and high dose intravenous immunoglobulin in a patient with Isaacs' syndrome. Issue 7 (July 1994) - Ishii, A; Hayashi, A; Ohkoshi, N; Oguni, E; Maeda, M; Ueda, Y; Ishii, K; Arasaki, K; Mizusawa, H; Shoji, S
Abstract : The clinical effects of plasma exchange and high dose intravenous immunoglobulin (IVIg) were evaluated in a 41 year old woman with Isaacs' syndrome. After double filtration plasma exchange, symptoms almost disappeared for two to three weeks and the recorded continuous muscle action potentials were considerably decreased. Symptoms recurred within a few months. On the other hand, IVIg worsened the symptoms of the disorder: during and after IVIg at a dose of 0.2 g/kg/day (total 50 g), widespread myokymia, pseudomyotonia, and muscle cramps gradually increased. Symptoms improved after another course of plasma exchange.